2023
DOI: 10.5772/intechopen.108475
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Derived from Commercial Fishing Activities

Abstract: Ordinary fishing activity is a source of microplastics to the sea that is often overlooked and scarcely reported in the literature. In this paper, we estimate the number of microplastics in the ocean that originates from the wear and tear of different fishing gear used during ordinary, commercial fishing. The wear comes mainly from rope abrasion caused by the haulers and gear dragged along the sea bottom. The types of fishing gear considered are pots, gillnets, longlines, Danish seine, and trawls. Our calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Fishery and aquaculture activities are considered potential sources of microplastics. Aquaculture materials such as plastic ropes, nets and fishing gear, which are common in fishing, can cause microplastic pollution in waters due to weathering or breakdown [10]. Additionally, various meteorological and hydrodynamic events have the capacity to strongly affect microplastic levels in freshwater and marine systems [7].…”
Section: Sea-based Sourcesmentioning
confidence: 99%
“…Fishery and aquaculture activities are considered potential sources of microplastics. Aquaculture materials such as plastic ropes, nets and fishing gear, which are common in fishing, can cause microplastic pollution in waters due to weathering or breakdown [10]. Additionally, various meteorological and hydrodynamic events have the capacity to strongly affect microplastic levels in freshwater and marine systems [7].…”
Section: Sea-based Sourcesmentioning
confidence: 99%
“…Syversen et al showed that between 77 and 97 tons of plastics are added to the sea annually in Norway from wear and tear during Danish seining [103]. The Norwegian fisheries in general are estimated to release about 208 tons of MNPs per annum [104].…”
Section: Mnps From Water Runoffmentioning
confidence: 99%